(untitled) (Fiep Bulletin - online, 2015)
Abstract: The purpose of this study was to investigate postoperative pain behavior referred to by patients submitted to thoracotomy according to the analgesic prescribed. Methodology: descriptive, transversal study, performed at two hospitals associated to the Brazilian National Health System (SUS), with a sample composed of 40 patients, 24 males and 16 females, mean age of 48.9 years. The instruments used were a physical therapy assessment form, numerical pain scale and McGill’s questionnaire. The procedures were performed by applying the instruments, then the numerical scale was shown to the patients, who selected the number from zero to ten that best exemplified their pain and finally the McGill questionnaire was read so that patients could choose the descriptor that best characterized their pain at that moment. After pain assessment, the prescribed analgesics were recorded. Results: A diversification of analgesic prescriptions was observed for patients submitted to thoracotomy and on both the numerical scale and McGill’s questionnaire there was a predominance of moderate pain in 40% of patient responses. However, the pain showed a tendency toward intense in 22.5% on the numerical scale and 35% on McGill. Conclusion: A lack of consensus and analgesic protocols in the postoperative following thoracotomy was verified, which shows that pain continues to be under-treated.